Genetic relationship among buffalo breeds of India - VIJH, R K; TANTIA, M S; MISHRA, BINA; KUMAR, S T BHARANI; VIJ, P K; SIROTHI, A R; SINGH, K P; KHARADI, VB; GAJBIDYE, P J; IYUEIO, M; GUJJAR, B V (The Indian Journal of Animal Sciences, 2011)
Microsatellite data were generated on 22 heterologous microsatellite loci in 10 defined breeds and 2 local populations of buffalo to study genetic relationship. All the markers were highly polymorphic in buffaloes. The genetic distances and relationship among 12 breeds/populations were estimated based on allele frequencies and number of repeat units. Nei’s DA and Chord distances were utilized for construction of phylogenetic tree using Neighbour Joining algorithm. The study revealed closeness among Mehsana and Surti, Pandharpuri and Marathwada, Toda and Kalasthi, and Bhadawari and Tarai, which can be explained on the basis of geographic contiguity. Jaffarabadi was, however, distinctive from Mehsana and Surti and closely related to Murrah breed. There was similarity of genotypes between Kalasthi (local population of Andhra Pradesh) and Toda, which is considered to be threatened breed of buffalo. The study emphasizes the need to undertake conservation and improvement programmes by pooling genetically similar breeds to save on resources. Â